STUDY OF THE INFLUENCE OF MARINE HEATWAVES ON THE UPWELLING ON SOUTH JAVA IN 1982 â 2019 - Irhamsyah Haryanto, Fachri
The upwelling phenomenon is the rising water mass from the bottom layer to the top layer or surface. The upwelling area is characterized by an increase in chlorophyll-a and a decrease in the value of Sea Surface Temperature (SST). The upwelling phenomenon in South Java can change in terms of intensity due to anomalies that occur in the sea. One of the anomalies that can affect the upwelling phenomenon is the marine heatwaves phenomenon. This study aims to know the influence of marine heatwaves on upwelling in 1982 - 2019 in Southern Java. This study examines the value of SST in South Java for 38 years, the characteristics of marine heatwaves in South Java and the upwelling and its relation to the Indian Ocean Dipole (IOD) event. The data used in this study are SST data from the Copernicus official website, wind speed data from the Copernicus official website and Dipole Mode Index (DMI) data obtained from the NOAA official website. Detection of marine heatwaves uses daily SST value for 38 years, then the threshold is seen, namely the 90th percentile, if the SST value exceeds the threshold for 5 days it is a marine heatwave phenomenon. The upwelling phenomenon is known by calculating the upwelling index. The value of SST in South Java varies every month between 240C to 300C. The highest range of SST values in South Java occurred in March, April, May with values ranging from 280C to 300C. The lowest SST values were recorded in June, July, August with values ranging from 240C to 260C. The decline in the SST value that occurred in this month was an indication of an upwelling. The detection of the marine heatwave phenomenon was carried out in three domains. Based on the calculation results, it is known that there have been approximately 79 to 85 marine heatwaves in Domains 1,2, and 3 in 1982 – 2019. The marine heatwaves with the highest intensity in southern Java occurred in 1998 and 2010 with values reaching around 40C. Both of these years were affected by negative IOD. In addition to these two years, there was 2016 with the longest duration of marine heatwaves, reaching 200 days, this was due to a strong El Nino event along with the weakening of the west monsoon and followed by a negative IOD event. Marine heatwaves cause the SST value during upwelling to increase by 3.9% to 16.7% and also decrease the upwelling index value by 16.7% to 25% compared to normal conditions.